Identification of spatial data and ecology of Javan hawk-eagle's nest (Nisaetus bartelsi) in the Kondang Merak Coastal, South Malang, East Java, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Iskandar RRD, Elfidasari D, Prawiradilaga DM. 2022. Identification of spatial data and ecology of Javan hawk-eagle's nest (Nisaetus bartelsi) in the Kondang Merak Coastal, South Malang, East Java, Indonesia. Biodiversitas 23: 3419-3428. Ecological identification of the Javan hawk-eagle's habitat (Nisaetus bartelsi) is necessary to understand the support of its life, such as the spatial data in connection with its home range, nest location, and the use of nest trees. The species must choose a location that suits its needs. According to several studies, The Javan hawk-eagle's presence was only in highland forests. The new report of The Javan hawk-eagle occurrence in Merak Kondang coastal confirmed The Javan hawk-eagle's presence in lowland forest. The objective of this study was to identify the landscape characteristics that become the habitat preferences of The Javan hawk-eagle in Merak Kondang coastal, South Malang, East Java. Analysis used in this study included habitat suitability maps, plant vegetation, spatial analysis of tree canopy, and tree nest architecture analysis. The home range of the Javan hawk-eagle in the Kondang Merak coastal, South Malang, East Java, covered an area of 149.94 Ha. Most of the home range overlapped between Javan hawk-eagle individuals, including siblings and between an individual Javan hawk-eagle with other species of eagle. The Javan hawk-eagle used Spondias pinnata as nest trees with the architectural model Scarrone. It used 3 different tree species for perching, namely Pterocymbium javanicum, Anthocephalus cadamba, and Alstonia angustiloba. In the tree phase, the dominant vegetation type was Spondias pinnata (IVI) 43,16%, the pole phase that dominates was Mallotus paniculatus (IVI) 62.31%, the dominant vegetation of the stake phase was Garcinia forbesii, and the seedling phase was Arenga obtusifolia (IVI) 71.42%. The highest diversity index (H') was in the tree phase (H’=2,34), which was in the moderately abundant category and was at an elevation of 8% (flat).
Keywords: Habitat, Javan hawk-eagle, nest tree, Nisaetus bartelsi, spatial data